RENCANA PENGEMBANGAN BISNIS PT WISMAN TUR CABANG GUNTUR MELALUI KONSEP PRIVATE TOUR - Vallerie Monica; Erwin Suryadi (Prosiding Working Papers Series In Management, 2017)
PT Wisman Tur at Guntur is a travel agency that has been established since 2008 at jln Guntur no 43, Jakarta Selatan. PT Wisman Tur sells a variety of flight tickets, hotel vouchers, tourist attractions tickets, and services to make an important tourist documents such as visas, passport, etc. After doing research with questionnaire and interview method, it is known that business Mr Yanto facing problem, that is not achieved sales target. In solving the problem, he proposed a concept of private tour business development to overcome the shortcomings of the problems that occurred. Development is done by making travel packages in private where travel plans, hotels tailored to the budget and consumer desires. With this development, PT Wisman Tour Branch OfGuntur can generate sales increase of Rp 2,119,879,723 at the end of 2017 with the capital of the owner of Rp 350,000,000.Keywords: Travel Agency, Private Tour